(untitled) (Annals of Medical Research, 2021)
Aim: This study was conducted to assess the awareness of women about cervical cancer and human papilloma virus (HPV) and to evaluate their HPV DNA test results. Materials and Methods: This analytical cross-sectional study was conducted in 250 women who applied to Cancer Early Diagnosis Screening and Training Center (KETEM) at Konya Training and Research Hospital of Health Sciences University. A questionnaire prepared by the researchers was applied to determine the women’s sociodemographic characteristics, cervical cancer and HPV knowledge levels. Results: The mean age of the women was 47.7 ± 7.5 years old. When the smear results of the women included in the study are examined, HPV was positive in 3.2% (n=8). Participants with higher education levels had significantly higher Pap smear test knowledge and performed more Pap smear tests than those who had lower education levels (p<0.001). Participants with higher monthly income had significantly higher levels of HPV vaccination knowledge (p=0.014). Women who had regular gynecological examinations, had higher screening test knowledge and had Pap smear tests more than those who were not screened regularly (p<0.001). Participants who know what is a Pap smear test, had a significantly higher HPV vaccine knowledge (p<0.001). Women who had higher education levels had a significantly higher knowledge level about HPV-related lesions (p<0.001). Conclusions: Pap smear test rates, awareness and knowledge regarding HPV, cervical cancer and HPV vaccine were appeared to be very low in our study. It is possible to reduce disorders caused by HPV infection and cervical cancer incidence by improving awareness for cervical cancer and HPV infection, generalizing use of preventive measures, and extending participation to screening programs and HPV vaccination.